Experiences of Attachment Injury in Heterosexual Couple Relationships - Pelling, Cate; Arvay-Buchanan, Marla (Canadian Journal of Counselling and Psychotherapy, 2007)
The aim of this study was to explore the lived experience of women’s attachment injuries within heterosexual couple relationships. An interpretative, phenomenological approach (van Manen, 1990) was used in this exploratory study. Four women participated in three separate research interviews in order to illuminate the phenomenon of “attachment injury” within heterosexual couple relationships. The six themes that emerged from the study provide an in-depth understanding of the experience of attachment injury within heterosexual couple relationships. Results from this study are consistent with research findings in the literature on attachment and on traumatic loss.